2021
DOI: 10.1111/jfr3.12716
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Hurricane Harvey flood event through coupled hydrologic‐hydraulic models: Challenges and next steps

Abstract: Using the 2017 Hurricane Harvey flood event as a test case, this study set up a series of sensitivity analyses to highlight three challenges associated with large‐scale flood inundation modeling, including (a) model parameterization, (b) errors in digital elevation models, and (c) effects of reservoir retention. Driven by radar‐based hourly rainfall data, a series of hydrologic‐hydraulic models including the VIC hydrologic model, RAPID routing model, and Flood2D‐GPU hydrodynamic model are set up over Harris Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 64 publications
(91 reference statements)
2
21
0
Order By: Relevance
“…A preliminary comparison showed that the LIS-HyMAP driven inundation is underestimated compared to the observation-based ORNL TRITON hindcast results Dullo et al [2021b], where ST4-VIC-RAPID driven TRITON produces higher flood inundation depths across the domain. The main difference is likely due to the lower simulated precipitation (i.e., modeled vs. ST4 observation) used to drive LIS-HyMAP.…”
Section: Subtask 1: Benchmark Simulation and Modeling Framework Asses...mentioning
confidence: 93%
See 2 more Smart Citations
“…A preliminary comparison showed that the LIS-HyMAP driven inundation is underestimated compared to the observation-based ORNL TRITON hindcast results Dullo et al [2021b], where ST4-VIC-RAPID driven TRITON produces higher flood inundation depths across the domain. The main difference is likely due to the lower simulated precipitation (i.e., modeled vs. ST4 observation) used to drive LIS-HyMAP.…”
Section: Subtask 1: Benchmark Simulation and Modeling Framework Asses...mentioning
confidence: 93%
“…In addition to the research tasks, we have also started to set up some modeling tools on Miller, the AF HPC11 system at ORNL, which will eventually be used to conduct the operational flood and inundation forecasting. Three peer-reviewed journal papers were accepted/published in the past project year (Morales-Hernández et al [2021], Dullo et al [2021b], Dullo et al [2021a]). In addition, Sharif et al [2020] received the Best Paper Award in the 2020 Platform for Advanced Scientific Computing Conference (PASC20).…”
Section: Performance Execution Planmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Dullo et al. (2021) also documented differences between Houston Metro bathymetry captured by a 10 m resolution DEM and estimates inferred from gage information. As a result, we applied a bathymetric error correction to the DEM as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The methodologies developed in recent decades to calculate rainfall thresholds responsible for triggering floods are based on the use of distributed and semi-distributed hydrological models [23,24]. The combination of a hydrological study and a hydraulic model not only allows to accurately predict the design hydrographs of the basin but, very important, consent to simulate flooding in the alluvial plain in order to analyze the specific terrain response to flooding [25,26]. This combined methodological approach is particularly useful in the case of ungauged rivers where in-situ measurements of river critical levels as well as flood susceptibility maps are lacking.…”
Section: Introductionmentioning
confidence: 99%